POSSIBLE CONSEQUENCES OF THE COVID-19 PANDEMIC ON THE MENTAL HEALTH OF EMPLOYEES IN TRAVEL AGENCIES IN SERBIA - Vučković, Jelisaveta; Ana, (The Business of Tourism, 2020)
On March 11, 2020, the World Health Organization declared COVID-19 virus pandemic, which is still ongoing, and it is uncertain when it will end. Essentially, it is an epidemiological problem which has turned into economic, sociological, socio-political and psychological one. Based on the information available so far, it can be concluded that the tourism industry (and within it, especially the business operations of travel agencies and tour operators), both in the world and in Serbia, is one of the most affected, due to the pandemic. Freedom of movement is restricted and people's safety is endangered, which are the key preconditions for tourism mobility. The subject of analysis in this paper is an attempt to look at the psychological aspect of the COVID-19 virus pandemic, with special emphasis on its possible consequences on the mental health of the employees in travel agencies in Serbia. The general opinion of the professionals is that it will undoubtedly adversely affect people's mental health, and prospective studies on this topic will follow in the future.
Keywords: COVID-19 virus pandemic; employees; mental health; travel agencies